PENGARUH TINGKAT BAGI HASIL DAN BI RATE TERHADAP BESARNYA TABUNGAN MUDHARABAH PADA BANK SYARIAH PERIODE 2013-2018 - Falahuddin Falahuddin; Muchsal Mina (Jurnal Akuntansi dan Keuangan, 2019)
This study aims to analyze the Effect of Profit-Sharing Rate and BI Rate on the amount of Mudharabah Savings in Islamic Banks from 2013 to 2018. This study uses secondary data in the form of Islamic Bank financial statements accessed on www.idx.com. The data analysis method used is multiple linear regression analysis. The sample used in this study is 12 banks. The results show that the profit-sharing rate partially has a positive and significant effect on Mudharabah savings in Islamic banks in Indonesia, the BI rate has no effect on Mudharabah savings in Islamic banks in Indonesia. Simultaneously, the profit-sharing rate and BI rate have a positive and significant effect on Mudharabah savings in Islamic banks in Indonesia.